THE RESEARCH PROJECT OF THE SOCIOLOGY OF KNOWLEDGE AS AN EXPERIMENT OF THE DIDACTICS OF SOCIOLOGY - Poviliūnas, Arūnas; Voznikaitis, Antanas; Bielevičiūtė, Indrė; Navickaitė, Sandra; Stulginskaitė, Paulė (Sociologija. Mintis ir veiksmas, 2016)
The article in the framework of teaching research describes the didactic dimension of the project of the sociology of scientific knowledge. Based on sociological investigation of the academic field, it attempts to conceptualize the formation of the habitus of the sociological research. The identification of the sociological habitus is treated as epistemological break, which is followed by epistemological vigilance. The analysis of the chemist academic community reveals not only the unique but also invariant aspects academic field that also shape the field of sociology. The recognition of the specific and isomorphic structure of academic field is considered as entrenchment of the sociological habitus.